2013
DOI: 10.2478/v10247-012-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil water evaporative loss after tillage operation using the stable isotope technique

Abstract: A b s t r a c t. Application of stable isotopes in soil studies has improved quantitative evaluation of evaporation and other hydrological processes in soil. This study was carried out to determine the effect of tillage on evaporative loss of water from the soil. Zero tillage and conventional tillage were compared. Suction tubes were installed for soil water collection at the depths 0.15, 0.50, and 1.0 m by pumping soil water with a peristaltic pump. Soil water evaporation was estimated using stable isotopes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Moreover, the presence of sufficient CR on the soil surface enhances SWS in two ways, by minimizing water loss by evaporation from the soil surface [52,81,238] and by reducing the negative impacts of raindrops by preventing the deformation of the soil aggregates and erosion [236,239]. In contrast, in Conv-A, when raindrops hit the unprotected soil surface, soil aggregates are destroyed to individual soil particles that clog the pores, impeding water to infiltrate the soil, and hence, it may increase runoff, soil erosion, and SWS.…”
Section: Effects Of Ca-practices On Soil Water-savingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of sufficient CR on the soil surface enhances SWS in two ways, by minimizing water loss by evaporation from the soil surface [52,81,238] and by reducing the negative impacts of raindrops by preventing the deformation of the soil aggregates and erosion [236,239]. In contrast, in Conv-A, when raindrops hit the unprotected soil surface, soil aggregates are destroyed to individual soil particles that clog the pores, impeding water to infiltrate the soil, and hence, it may increase runoff, soil erosion, and SWS.…”
Section: Effects Of Ca-practices On Soil Water-savingmentioning
confidence: 99%
“…In such situations, Conv-A can increase infiltration rate and SWS more than CA-based management systems [241,242]. The higher soil water content under CA-based management practices (Table 4) has been linked to lower soil temperature and lower evaporation from the soil surface [101,238]. Parihar et al [52] found that CA-practices reduced evaporation by 23%-37% compared to Conv-A.…”
Section: Effects Of Ca-practices On Soil Water-savingmentioning
confidence: 99%
“…Other researchers Kader et al (2017) also found that straw mulching helped to conserve soil moisture at a 0-30 cm depth and reduced soil temperature. The main explanation might be linked to lower soil temperatures and lower evaporation from residue retention plots (Busari et al, 2013). However, the trend of increased SMC owing to CA management practices is highly dependent on the regional climate (Abdallah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotopes ( 2 H and 18 O) in soil water are a sensitive indicator of water loss by evaporation because evaporation enriches soil water in heavy isotopes while root water uptake and subsurface leakage do not (Al‐Oqaili, Good, Peters, Finkenbiner, & Sarwar, 2020; Soderberg, Good, Wang, & Caylor, 2012; Wang et al., 2012). This property has propelled stable isotopes to be an established method for soil water flux monitoring (Busari et al., 2013) and the partitioning of moisture losses (Al‐Oqaili et al., 2020). Van den Akker, Simmons, and Hutson (2011) found differences in isotope enrichment among irrigation bays due to evaporation losses driving isotope enrichment within the local pan at different stages of irrigation.…”
Section: Introductionmentioning
confidence: 99%